2016
DOI: 10.1002/ijc.30145
|View full text |Cite
|
Sign up to set email alerts
|

Serum pepsinogen levels can quantify the risk of development of metachronous gastric cancer after endoscopic resection

Abstract: We have previously reported that serum pepsinogen (PG) can quantify the level of gastric mucosal atrophy, and that H. pylori eradication reduces cancer development in subjects with mild atrophy identified by serum PG levels. The aim of this study was to elucidate the predictive ability of serum PG levels for the development of metachronous gastric cancer (MGC) after endoscopic resection (ER) of primary cancer in association with H. pylori eradication. A retrospective chart review was performed, and 330 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 35 publications
0
18
0
1
Order By: Relevance
“…Atrophic gastritis in the corpus or intestinal metaplasia is considered to be a risk factor for the development of GCAE. [59][60][61][62][63][64] In 2015, the Kyoto Global Consensus Conference on H. pylori gastritis was held and the following statement was accepted: patients who remain A B C D Fig. 2.…”
Section: Possible Risk Stratification For Development Of Gastric Cancmentioning
confidence: 99%
“…Atrophic gastritis in the corpus or intestinal metaplasia is considered to be a risk factor for the development of GCAE. [59][60][61][62][63][64] In 2015, the Kyoto Global Consensus Conference on H. pylori gastritis was held and the following statement was accepted: patients who remain A B C D Fig. 2.…”
Section: Possible Risk Stratification For Development Of Gastric Cancmentioning
confidence: 99%
“…Since the measurement of serum PG levels is cost‐effective, minimally invasive, and quick and easy to perform, it has been considered to be suitable biomarker for gastric cancer screening in populations at high risk . Two Japanese studies showed that lower pre‐endoscopic submucosal dissection ratio of PGI:PGII were significantly associated with metachronous gastric cancer development regardless of H. pylori status. Together with this study, these observations suggest lower serum ratio of PGI:PGII (≤3 or 3.3) at time of endoscopic resection can be useful predictive biomarkers for assessing risk of metachronous gastric neoplasm development in patients undergoing endoscopic resection.…”
Section: Discussionmentioning
confidence: 99%
“…The Kimura-Takemoto classification is useful for determining cancer risk. Limitations include lack of routine use in western populations and moderate interobserver rating (94). This endoscopic method stratifies cancer risk by estimating atrophy extent and has not been included in either UK or international guidelines.…”
Section: Endoscopy Assessmentmentioning
confidence: 99%